Principles for guiding research and innovation toward sustainable and equitable agrifood systems - Zurek, Monika; Wirths, Jonathan; Hebinck, Aniek; Crawford, Scarlett; Lidder, Preetmoninder; Prasad, P. V. Vara; Tittonell, Pablo; Herrero, Mario; Compton, Julia (Frontiers in Sustainable Food Systems, 2023)
Investments in research and innovation are critical for transformations towards sustainable agrifood systems and for meeting the Sustainable Development Goals and the Paris Climate Agreement. However, the frequent neglect of environmental and social goals by investors remains a major challenge. System-oriented approaches to designing and monitoring innovations can be a promising solution to guide innovations and allow investors to identify those that are more sustainable. This article presents a set of eight ’Principles for Agrifood Research and Innovation’ developed by an international multi-stakeholder task force including staff of research agencies, funders and impact investors, private sector, non-governmental organisations, and benchmarking organisations. The article explains the rationale for the selection of the principles and describes potential ways forward for their uptake and implementation, building on pilots done by several research and funding organisations.